2013
DOI: 10.3109/0142159x.2013.836270
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and prevention of failure: An early intervention to assist at-risk medical students

Abstract: Close similarity between predictor task and target task is important for accurate prediction of failure. Consideration should be given to dose effect and class size in the prevention of failure of at-risk students, and we recommend a systemic approach to intervention/remediation programmes, involving a whole semester of mandatory, weekly small group meetings with experienced teachers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
64
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 44 publications
5
64
0
Order By: Relevance
“…A recent study reported on the administration of an exam already in week 2 of the program in order to identify at-risk students in a US-Caribbean medical school (Winston et al 2014). Of the students who failed this early exam, 65 % went on to fail one of the first three semesters in the program, corresponding to a positive predictive validity of 0.65.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…A recent study reported on the administration of an exam already in week 2 of the program in order to identify at-risk students in a US-Caribbean medical school (Winston et al 2014). Of the students who failed this early exam, 65 % went on to fail one of the first three semesters in the program, corresponding to a positive predictive validity of 0.65.…”
Section: Discussionmentioning
confidence: 98%
“…In addition to the paucity of studies on how to best identify students at risk at the earliest possible time, the literature also reveals how challenging the task of preventing failure long term is (Tekian and Hruska 2004;Devoe et al 2007;Stegers-Jager et al 2013), and currently there seems to be little evidence to support 'best practice' in remediation (Hauer et al 2009;Cleland et al 2013;Winston et al 2014). On the optimistic side, active learning curricula have been found to improve program completion rates and times (Iputo and Kwizera 2005;Schmidt et al 2009), and it seems that prevention and remediation strategies which encourage student participation and ownership are worth examining further (Cleland et al 2005, Stegers-Jager et al 2013Winston et al 2014;Bierer et al 2015;Patel et al 2015;Gonsalvez et al 2015).…”
Section: Perspectives and Future Researchmentioning
confidence: 97%
See 3 more Smart Citations